2018
DOI: 10.1002/ptr.6187
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of autophagy in the protective effect of resveratrol on PM2.5‐induced pulmonary oxidative injury in mice

Abstract: Ambient fine particulate matter (PM2.5) is capable of inducing pulmonary oxidative injury. Autophagy maintains basal cellular homeostasis and plays a critical role in the pathogenesis of lung diseases. Resveratrol, a natural polyphenol, is an effective antioxidant agent against particulate matter (PM)-induced injuries. The current study was designed to investigate whether resveratrol can regulate autophagy in the process of PM2.5-mediated pulmonary oxidative injury. In the mice model of PM2.5 exposure, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Other potential SOA-mediated mechanisms could be envisioned if we reason that SOA are part of PM. It has been demonstrated that PM, especially PM2.5, have the capacity to reduce cell proliferation , through cell cycle arrest in different types of cells. ,,, PM are also known to induce apoptosis and autophagy. , Interestingly, a crosstalk between the latter has been documented, , and both can be explained by PM2.5 implication concerning a decrease of mRNA and protein level of mammalian target of rapamycin (mTOR). Quite relevant, PM2.5-induced apoptosis was found to be mediated by an increase of known apoptotic factors like p53 and a decrease of its inhibitor, SGK1 usually activated by mTOR, resulting in a cascade of different steps and involving a series of molecules such as Bax, cytochrome c , APAF-1, and caspases (Figure ). Of course, additional studies are required in order to determine the relevance of these speculations.…”
Section: Pathogenic Impact Of Soamentioning
confidence: 99%
“…Other potential SOA-mediated mechanisms could be envisioned if we reason that SOA are part of PM. It has been demonstrated that PM, especially PM2.5, have the capacity to reduce cell proliferation , through cell cycle arrest in different types of cells. ,,, PM are also known to induce apoptosis and autophagy. , Interestingly, a crosstalk between the latter has been documented, , and both can be explained by PM2.5 implication concerning a decrease of mRNA and protein level of mammalian target of rapamycin (mTOR). Quite relevant, PM2.5-induced apoptosis was found to be mediated by an increase of known apoptotic factors like p53 and a decrease of its inhibitor, SGK1 usually activated by mTOR, resulting in a cascade of different steps and involving a series of molecules such as Bax, cytochrome c , APAF-1, and caspases (Figure ). Of course, additional studies are required in order to determine the relevance of these speculations.…”
Section: Pathogenic Impact Of Soamentioning
confidence: 99%
“…In vascular endothelial cells, autophagy-induced by PM 2.5 decreases cell cytotoxicity (Zhou et al ., 2018). In addition, compounds such as resveratrol protect lung cells from PM-induced oxidative injury by inducing autophagy (Li et al ., 2018). However, to date, there have been no studies on the relationship between PM-induced autophagy and AhR activation.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is a natural plant antitoxin that can protect against fungal infections, and is also an active ingredient in some herbs that possess capacity to treat inflammation, lipid metabolism, and heart disease [4,5]. Additionally, resveratrol is also documented to have antioxidant, anti-inflammatory, and anti-tumor activities [68]. More importantly, resveratrol has been reported to protect against muscle injury [912].…”
Section: Introductionmentioning
confidence: 99%